2005
DOI: 10.4049/jimmunol.175.1.139
|View full text |Cite
|
Sign up to set email alerts
|

Liver Sinusoidal Endothelial Cells Tolerize T Cells across MHC Barriers in Mice

Abstract: Although livers transplanted across MHC barriers in mice are normally accepted without recipient immune suppression, the underlying mechanisms remain to be clarified. To identify the cell type that contributes to induction of such a tolerance state, we established a mixed hepatic constituent cell-lymphocyte reaction (MHLR) assay. Irradiated C57BL/6 (B6) or BALB/c mouse hepatic constituent cells (HCs) and CFSE-labeled B6 splenocytes were cocultured. In allogeneic MHLR, whole HCs did not promote T cell prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
56
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 53 publications
7
56
1
Order By: Relevance
“…5A), in accordance with the work of Onoe et al (79). Since various MHC-II-negative cell types conditionally express MHC-II upon activation by cytokines, by gamma interferon in particular (106), we surmised that the MHC-II ϩ…”
Section: Cd146supporting
confidence: 69%
See 1 more Smart Citation
“…5A), in accordance with the work of Onoe et al (79). Since various MHC-II-negative cell types conditionally express MHC-II upon activation by cytokines, by gamma interferon in particular (106), we surmised that the MHC-II ϩ…”
Section: Cd146supporting
confidence: 69%
“…Whereas LSECs were reported to constitutively express MHC-II as well as CD11c, sharing these markers with DCs (reviewed in references 57 and 67), Katz and colleagues presented conflicting results showing low or absent expression of both MHC-II and CD11c by LSECs (50). To make confusion perfect, Onoe and colleagues (79) concluded that murine LSECs express MHC-II but not CD11c. Importantly, as shown above (Fig.…”
Section: Donor-derived Mhc-iimentioning
confidence: 99%
“…33 In healthy, adult animals, CD105 is mainly expressed in the distal arteries, distal veins, and capillaries of lung and liver. 22,28,34 The pronounced preference of mCD105-LV particles for liver LSECs is most likely due to a combination of vector particle properties, blood circulation kinetics, and accessibility of the CD105 receptor for the vector particles present in the lumen of the blood vessels. We know from previous work with huCD105-LV, 9 but also other targeting vectors, 12 that transduction efficiency closely correlates with the cell surface density of the targeted receptor.…”
Section: Discussionmentioning
confidence: 99%
“…However, at least for stellate cells, which have been defined as CD105-positive by biochemical data, 25 the CD105 density must be much lower than that on LSECs, because these can be easily purified from liver using CD105-specific antibodies. 22 In addition, stellate cells are rather inaccessible for systemically applied mCD105-LV because these For personal use only. on June 7, 2019.…”
Section: Discussionmentioning
confidence: 99%
“…Transmigrating T cells might rapidly remigrate, receive suppressive signals upon transmigration, 43,44 or subsequently interact with tolerogenic Ito cells. 45 In this respect, endothelial cells from the liver sinusoids seem to possess a special feature in facilitating T cell balance and immune surveillance under homeostatic conditions and presumably even more strongly under inflammatory conditions.…”
Section: Discussionmentioning
confidence: 99%